Queer Phenomenology and the Things Themselves in Eavan Boland’s In a Time of Violence - Haines, Aubry (ABEI Journal, 2021)
Situating Eavan Boland’s In a Time of Violence in dialogue with Sara Ahmed’s Queer Phenomenology, this article contends that Boland’s ekphrastic portrayals of physical things queers both traditional phenomenological conceptions of being-in-the-world as well as numerous conventions in Irish poetry. Eavan Boland’s concern for objects throughout the volume undermines widespread literary depictions of Irish women as essentialized, mythologized, or emblematized figures. Her preoccupation with physical things allows her to reject acts of reductive, discursive violence so often perpetrated by past male Irish authors and poets. Boland chooses to focalize upon quotidian, pedestrian, and overlooked objects, thus naturally aligning her poetry with Sara Ahmed’s Queer Phenomenology. Both Boland and Ahmed rescue marginalized perspectives from the darkened corners of existence. Boland’s poetry demonstrates an acute awareness that returning to “the things themselves” (Husserl 18) provides avenues for reclamation, multiplicity, and autonomy in the face of hegemonic, anonymizing narratives of Irish femininity.